Membangun Sosialisasi Masyarakat Melalui Nonton Bersama Warga Desa Emplasmen Kwala Mencirim - Sirait, Hanifah Rahmi; Siregar, Mutiara Anjani; Winda, Tamara; Panjaitan, Saiful Abdi; Harahap, Zuhrina; Tarmizi, Muhammad (SIMAS: Jurnal Pengabdian Masyarakat, 2024)
The film is set in the 1970s in Bangka Belitung, which is famous for its lead mines. The film shows friendship, family, education, limitations, and morality. The Rainbow Laskar tells the spirit of the struggle to get an education for the children of the village with limited resources and to establish a school that remains operational with moral, moral, and aqidah priorities. It's interesting to study such phenomena as education, morality, underprivileged students, and some of the phenomenon that became the film's icon. This research uses an inductive qualitative approach, which means creating concepts based on existing data. By analyzing the waterfall approach directly with local villagers, and inviting the community around to watch the film Rainbow Laskar in the Emplasmen Village of Kwala Mencirim.